Competências do gerente de projetos e empregabilidade: um estudo com gerentes de projeto de uma instituição bancária multinacional - Oliveira Junior, José Domingues de (2013)
This work proposes a study aiming to analyze and identify among the skills needed for project management and raised in the literature, which correlate more with the view of employability project manager. Therefore a quantitative survey research (survey) was conducted, with information technology project managers work in a bank of international origin, and with support from professional organizations and academic related to this type of professional. From the literature, were related individual and organizational competencies assigned to the project managers. This theoretical framework, together with an internationally validated scale for measuring employability, gave the instrument to collect data. As a result, it was found that there is a relationship between skills - technical, social and business – of project managers, and employability. This result of this study will have the following contributions: for the companies, the study may help in identifying the skills to be exploited in organizations or improving management models; use by companies of the information from this study to improve the training of project managers; identifying the skills that the manager already active in the area sees as promoting employability, which can be used for project management courses to promote the integration of its professionals in the job market; identifying the skills that because they are not seen as promoting employability in the short term, may be being neglected in the personal and professional development of project managers, although they are listed in previous studies as needed for effective project management, and ultimately contribute to project managers understand the factors that lead to their greater or lesser employability in the area in which they operate. The result of this study may assist in building or maturing career of established professionals, as well as indicate to students the skills to be developed for an effective entry into the labor market.